You cannot be what you cannot see: a retrospective natural longitudinal cohort study exploring the impact of face-to-face rural immersion on student medical training satisfaction and intention to practice rurally - Srinivas Kondalsamy-Chennakesavan; Matthew R McGrail; Bushra F Nasir; Alan Bruce Chater (BMJ Open)
Objective Community-engaged immersive rural experiences were limited during the COVID-19 pandemic when online learning was instigated across medical institutions globally. This study aimed to explore the impact of online learning on medical students’ satisfaction levels and intentions to practice in a rural area after graduation.Design, setting and participants We conducted a natural quasi-experimental longitudinal retrospective cross-sectional study during 2011–2022 for all Australian domestic medical students who undertook a Rural and Remote Medicine (RRM) placement at the University of Queensland. Anonymous administrative course evaluation data were collected for the same two questions in each cohort over 12 years, between 2011 and 2022.Outcome measures Change in students’ intention to pursue a rural medical career and teaching and placement satisfaction levels was determined. Longitudinal data illustrated trends in students’ intention and overall satisfaction across cohorts before and during COVID-19 disruptions.Results 2695 students participated in the surveys with an average response rate of 81%. Intention levels remained steady between 2011 and 2019, during which students experienced a consistent face-to-face orientation and rural placement immersion. During the COVID-19 disruption phase, primarily in 2020 and 2021, students’ intention to pursue a rural medical career significantly decreased when online-only learning placements were implemented, with only 25% of students in the most impacted rotation indicating a strong positive intention, compared with a previous steady 75%. Comparatively, students’ satisfaction with the RRM programme remained steady across all the years at about 85–90%.Conclusions There appears to be a detrimental impact of a lack of immersive community-engaged education experiences on medical student’s intention to pursue a rural medical career. This natural experiment demonstrates that while online learning maintains student satisfaction levels, it lacks value and authenticity and does not inspire students to consider future rural careers. The value of face-to-face and immersive community-engaged experiences is fundamentally an important contributor to inspiring students to work in rural areas in the future.